2018
DOI: 10.2337/dc18-0342
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c and Hypoglycemia Reductions at 24 and 52 Weeks With Sotagliflozin in Combination With Insulin in Adults With Type 1 Diabetes: The European inTandem2 Study

Abstract: In a 1-year study, sotagliflozin was associated with statistically significant HbA reductions. More episodes of DKA and fewer episodes of documented and severe hypoglycemia were observed in patients using sotagliflozin relative to those receiving placebo (ClinicalTrials.gov, NCT02421510).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
251
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(266 citation statements)
references
References 33 publications
12
251
0
3
Order By: Relevance
“…The results of this dose‐ranging study were confirmed in three larger, previously published, phase 3 trials, in which sotagliflozin significantly reduced HbA1c, weight and SBP with lower bolus and total insulin doses . A pooled analysis of data from the inTandem1 and inTandem2 studies confirmed the PPG reductions seen in the present study .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of this dose‐ranging study were confirmed in three larger, previously published, phase 3 trials, in which sotagliflozin significantly reduced HbA1c, weight and SBP with lower bolus and total insulin doses . A pooled analysis of data from the inTandem1 and inTandem2 studies confirmed the PPG reductions seen in the present study .…”
Section: Discussionsupporting
confidence: 87%
“…All patients received urine ketone strips and blood BHB meters and strips, as well as instructions on detecting and treating ketosis, urogenital hygiene, and proper hydration. Study centres received recommendations for ketosis and DKA diagnosis and management, as detailed in the phase 3 sotagliflozin trial reports (inTandem1, 2 and 3) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ClinicalTrials was also searched and no additional clinical trials with reported results could be found. Finally, in total, 13 eligible studies with 5397 participants (3364 participants in intervention groups vs 2033 participants in control groups) were enrolled, including two articles in one RCT for canagliflozin, four articles for dapagliflozin, four articles for empagliflozin (three articles in one RCT) and six articles for sotagliflozin . Most of the articles showed a relative low risk bias, but other bias with a higher risk was because nine studies were funded …”
Section: Resultsmentioning
confidence: 99%
“…The STOP DKA Protocol has many recommendations that align with those in previously published DKA risk mitigation documents . One of the unique features of the STOP DKA Protocol is that it emphasizes a stepwise approach that takes its cue from the patient's glycaemia and ketone status.…”
Section: Use Of Sglt Inhibitors In Type 1 Diabetes and The Stop Dka Pmentioning
confidence: 99%